Is the classification of Ventilator-Associated Pneumonia as early and late- onset useful? A comparison of Microbial Profile, Antibiotic Susceptibility and Mortality - SAMI UR REHMAN; UNAIZA SAEED; HUSNAIN BIN SAEED; SARAN GHANI; ARSHAD TAQI (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To see the microbial profile of early and late-onset ventilator-associated pneumonia, antibiotic susceptibility and mortality rate. Methods: Retrospective cross-sectional study in 18-month period from 1st January 2023 to 31st June 2024 in Surgical ICU of Doctors Hospital and Medical Centre, Lahore, Pakistan. Data was analyzed using the IBM SPSS 29.0 software, and an Excel sheet was used to make a table of isolates and their sensitivity to antibiotics. Descriptive statistics like standard deviation and mean are used. One sample t-test was applied. SPSS and Excel sheet files are provided with the text. The P-value was set at <0.05, and a confidence interval of 95% is taken. Results: A total of 46 ventilator associated pneumonia (VAP) were recorded during our study period of 18 months. Out of 46 cases, 13 (28.2%) were early-onset VAP and 33 (71.7%) were late-onset VAP. Males being more admitted in our surgical ICU, their number of VAP is also high, that is, 31(67.3%), while females constitute 15 (32.6%) cases. Among the early-onset VAP, the most common isolates were Pseudomonas aeruginosa 4(30.7%), Candida albicans 4(30.7%), Klebsiella pneumonia 2(15.38%), followed by each one of the Acinetobacter, Burkholderia, and E. coli. While in the late-onset VAP, isolates that appeared on tracheal cultures were Acinetobacter 8(24.2%), Klebsiella 8(24.2%), Pseudomonas 7(21.2%), Staphyloccus aureus 3(9.09%), Burkholderia 2(6.06%), Candida 2(6.02%), Proteus mirabilis 1(3.03%), E. coli 1(3.03%) and Enterobacter cloacae 1(3.03%). Almost all gram-negative organisms were sensitive to colistin except one E. coli. All Pseudomonas and Acinetobacter isolates were resistant to carbapenems (100% resistance), while Klebsiella is only 40% (4 out of 10) sensitive to carbapenems, E. coli 50% (1 out of 2), Burkholderia 66.6% (2 out of 3) and Proteus mirabilis was 100% sensitive. Klebsiella is 70% sensitive to chloramphenicol. Minocycline has 100% susceptibility for Acinetobacter, Enterobacter, and Staphylococcus aureus, while it has 60% susceptibility to Klebsiella and 33.3% for Burkholderia. Conclusion: At the end of this study period of 18 months, we conclude that VAP is mainly caused by MDR bacteria, especially Pseudomonas aeruginosa, Klebsiella pneumoniae, and Acinetobacter Baumanni, in our settings, irrespective of the duration of onset. We suggest that broad spectrum MDR cover, including colistin, along with gram positive cover like vancomycin, linezolid, or teicoplanin, should be started as an empirical therapy to prevent the onset of early or late VAP. Keywords: Ventilator associated pneumonia (VAP), Intensive Care Unit (ICU), Mechanical ventilation, Early Onset VAP, Late Onset VAP, Antimicrobial resistance